Determination of the Physical and Chemical Characteristics of Dry Cacao Beans (Nacional and CCN-51) in Collection Centers in Bolívar Canton (Agroindustrial Science, 2026)
The objective of this study was to evaluate the physical and chemical characteristics of dried cocoa beans from the Nacional and CCN-51 varieties in collection centers in the Bolívar canton, Manabí. A total of 120 samples were collected using an analytical-descriptive approach and an exploratory research design. The methodology included instrumental techniques such as precision balance, pH meter, and moisture meter, and statistical tests such as Shapiro-Wilk, Levene’s test, ANOVA, and Student’s t-test were applied. Among the most relevant results, significant differences were identified in variables such as testa and cotyledon pH, as well as seed index and cotyledon weight between the two varieties. The PPSEP2024 collection center showed high moisture levels, which could affect bean quality. In conclusion, it was evident that both genetic variety and post-harvest handling directly influence cocoa quality. These results provide key information to improve collection processes and strengthen the competitiveness of Ecuadorian cocoa in specialized markets.
Keywords: Quality; variety; fermentation; post-harvest; characterization